An investigation into linguistic features in vision statements of American and Vietnamese Universities - Nguyễn Khánh Phượng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
In this study, I aim to investigate linguistic features of vision statements in the visions of universities in the USA and Viet Nam. The linguistic features of the English and Vietnamese clause in general in both languages in particular are considered in comparison to each other, then their semantic. This study is both qualitatively and quantitatively carried out with the analysis of one hundred and two visions in English and Vietnamese universities. The findings of this study show the frequency and variety in terms of occurrence of the different linguistic feature patterns in English and Vietnamese visions of the universities along with observations, discussion and explanations for the findings. The results of this work are applicable to the linguistic features and the use translation of visions for research, studying and communication purposes.